1996
DOI: 10.1088/0026-1394/33/4/19
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological interpretation of impurity redistribution effects on the freezing curve of oxygen

Abstract: Double freezing curves of oxygen have been obtained in a cooling process with a rate of less than 40 mK/min. The plateaus of these double freezing curves show differences in temperature and width. The cause of the observed double freezing curve is presumably redistribution of impurities into relatively pure and impure regions by transportation during the slow cooling process. This separation is observed in the melting curve of oxygen using both continuous and pulse heating methods. We note the importance of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The split indicates that two separate N&G processes are occurring in series. Kang et al observed a similar split in the freezing curve of solid oxygen [9] and explained their results in terms of the redistribution of impurities. We speculate that our results could be explained by the same mechanism, although this has not been confirmed.…”
Section: Freezing Behaviour Of the Pd Cellmentioning
confidence: 71%
“…The split indicates that two separate N&G processes are occurring in series. Kang et al observed a similar split in the freezing curve of solid oxygen [9] and explained their results in terms of the redistribution of impurities. We speculate that our results could be explained by the same mechanism, although this has not been confirmed.…”
Section: Freezing Behaviour Of the Pd Cellmentioning
confidence: 71%